On the Shoulders of Giants (Res Medica, 2014)
Cullen, Syme, Simpson, Lister, Littlejohn, Lauder Brunton, Dunlop; all names synonymous with the history of medicine, all names synonymous with the history of Edinburgh medicine, all names synonymous with the history of the Royal Medical Society.